PENGARUH MODEL PEMBELAJARAN PBL BERBANTUAN ICE BREAKING TERHADAP KEMAMPUAN REPRESENTASI MATEMATIS DAN KEMANDIRIAN BELAJAR SISWA KELAS VIII MTs ZIA SALSABILA - Maulia Fariha; Isran Rasyid Karo-Karo S (Universitas Bhinneka PGRI, 2024)
This study aims to determine the effect of the Problem Based Learning learning model assisted by ice breaking on students' mathematical representation abilities and learning independence. The method used is a quantitative method with an experimental research type. The sample consists of 27 students of VIII B as an experimental class and 20 students of class VIII A as a control class at MTs Zia Salsabila Bandar Setia. The results of the study showed that the t-test analysis that had been carried out obtained a p-value = 0.00 0.05 and p-value = 0.0001 0.005. The data explains that is accepted and is rejected. The average n-gain obtained in the experimental class was 0.64 and 0.57 while the control class obtained a value of 0.16 and 0.29 so that the average difference in n-gain was 0.48 and 0.28. Based on these data, it can be concluded that the mathematical representation ability and learning independence of students who learn using the PBL learning model assisted by ice breaking are better than students who learn in class with conventional learning models. There is an influence of the use of the PBL learning model assisted by ice breaking on students' mathematical representation abilities and learning independence.